The Formation of the Image of China in the Context of School Textbooks on the History of Kazakhstan - Kishibayeva, S.B.; Mengjie, Shan (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2025)
History textbooks play a crucial role in history education and are an important tool for imparting historical knowledge and developing historical consciousness. This study explores the formation of historical consciousness in Kazakhstan from secondary school history textbooks. Since the content of history textbooks for grades 10 and 11 is a review and integration of the content of grades 5 to 9, the sample of the study in this paper was selected from history textbooks for grades 5 to 9 in Kazakhstan. The study analyzes the content of Kazakhstan's secondary school history textbooks for grades 5-9 on the relations between China and the Kazakhstan region from ancient times to the present day, explores the past, present, and future of the relations between the two countries, describes the impact of Kazakhstan's secondary school history textbooks on the formation of the population's historical consciousness. The existence of numerous historical materials proves that the relations between China and Kazakhstan have a long history. Nowadays, under the auspices of the Belt and Road cooperation initiative, the prospects for the development of relations between the two countries are optimistic. The narratives about China in the history textbooks of Kazakhstan's secondary schools make it possible for students to implicitly accept China's influence and participation in the historical development of Kazakhstan's region, as well as to make the relationship between the two countries a part of the construction of the national identity of modern Kazakhstan and a part of the population's historical consciousness.